Two ways to one goal: new strategy of antiviral therapy for chronic hepatitis C - S. N. Batskikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze data of the clinical studies on chronic hepatitis C (CHC) treatment with application of new modes of combined therapy, including selective inhibitor of viral protease.Key points. New algorithms of antiviral therapy for patients infected by the 1-st virus genotype not treated earlier, and after treatment failure, implicate presence or absence of so-called «induction phase», the kernel of which is application of pegilated interferon-α and ribavirin combination at the beginning of treatment with subsequent addition of the third agent (the direct action antiviral agent). Triple therapy with induction phase strategy is recommended at application of boceprevir as the third agent. Another antiviral drug with direct action – telaprevir is recommended for prescription from first day of treatment.Conclusion. Taking into account an apparent positive effect of induction phase for boceprevir modes of treatment and absence of that evidence for telaprevir application, both new antiviral strategies are justified for clinical application in CHC patients.